An Artificial Intelligent Signal Amplification System for in vivo Detection of miRNA - Ma, Xibo; Chen, Lei; Yang, Yingcheng; Zhang, Weiqi; Wang, Peixia; Zhang, Kun; Zheng, Bo; Zhu, Lin; Sun, Zheng; Zhang, Shuai; Guo, Yingkun; Liang, Minmin; et al. (Frontiers in Bioengineering and Biotechnology, 2019)
MicroRNAs (miRNA) have been identified as oncogenic drivers and tumor suppressors in every major cancer type. In this work, we design an artificial intelligent signal amplification (AISA) system including double-stranded SQ (S: signal strand; Q: quencher strand) and FP (F: fuel strand; P: protect strand) according to thermodynamics principle for sensitive detection of miRNA in vitro and in vivo. In this AISA system for miRNA detection, strand S carries a quenched imaging marker inside the SQ. Target miRNA is constantly replaced by a reaction intermediate and circulatively participates in the reaction, similar to enzyme. Therefore, abundant fluorescent substances from S and SP are dissociated from excessive SQ for in vitro and in vivo visualization. The versatility and feasibility for disease diagnosis using this system were demonstrated by constructing two types of AISA system to detect Hsa-miR-484 and Hsa-miR-100, respectively. The minimum target concentration detected by the system in vitro (10 minutes after mixing) was one-tenth that of the control group. The precancerous lesions of liver cancer were diagnosed and the detection accuracy were larger than 94% both in term of location and concentration. The ability to establish this design framework for AISA system with high specificity provides a new way to monitor tumour progression and to assess therapeutic responses.